A pilot randomized controlled trial of cognitive bias modification to reduce fear of breast cancer recurrence. Issue 8 (5th January 2017) - Lichtenthal, Wendy G.; Corner, Geoffrey W.; Slivjak, Elizabeth T.; Roberts, Kailey E.; Li, Yuelin; Breitbart, William; Lacey, Stephanie; Tuman, Malwina; DuHamel, Katherine N.; Blinder, Victoria S.; Beard, Courtney
Abstract : BACKGROUND: The most common, persistent concern among survivors of breast cancer is the fear that their disease will return, yet to the authors' knowledge, few interventions targeting fear of cancer recurrence (FCR) have been developed to date. The current pilot study examined the feasibility, acceptability, and preliminary efficacy of a home‐delivered cognitive bias modification intervention to reduce FCR. The intervention, called Attention and Interpretation Modification for Fear of Breast Cancer Recurrence (AIM‐FBCR), targeted 2 types of cognitive biases (ie, attention and interpretation biases). METHODS: A total of 110 survivors of breast cancer were randomized to receive 8 sessions of 1 of 2 versions of AIM‐FBCR or a control condition program. Computer‐based assessments of cognitive biases and a self‐report measure of FCR were administered before the intervention, after the intervention, and 3 months after the intervention. RESULTS: Improvements in health worries ( P  = .019) and interpretation biases (rates of threat endorsement [ P <.001] and reaction times for threat rejection [ P  = .007]) were found in those survivors who received AIM‐FBCR compared with the control arm. Although only 26% of participants who screened into the study agreed to participate, the trial otherwise appeared feasible and acceptable, with 83% of those who initiated the intervention completing at least 5 of 8 sessions, and 90% reporting satisfaction with the computer‐based program used. CONCLUSIONS: The results of the current pilot study suggest the promise of AIM‐FBCR in reducing FCR in survivors of breast cancer. Future research should attempt to replicate these findings in a larger‐scale trial using a more sophisticated, user‐friendly program and additional measures of improvement in more diverse samples. Cancer 2017;123:1424–1433. © 2016 American Cancer Society . Abstract : Despite the high prevalence of fear of cancer recurrence among survivors, to the authors' knowledge, few interventions targeting this issue have been developed and evaluated to date. The current pilot randomized controlled trial demonstrates the feasibility, acceptability, and preliminary efficacy of a home‐delivered, computer‐based cognitive bias modification intervention targeting fear of cancer recurrence in survivors of breast cancer, and shows a significant reduction in health worries and interpretation biases among those participants randomized to receive active treatment.